Kekuatan Eksekutorial Putusan Mahkamah Konstitusi Yang Bersifat Final Dan Mengikat di Indonesia - Ru'ati, Amien; Nirahua, Garciano; Soplantila, Ronny (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: The Constitutional Court is a state institution that has judicial authority based on the 1945 Constitution which has the constitutional authority to conduct judicial review of the 1945 Constitution whose decisions are final and binding. However, in the implementation of the judicial review of the 1945 Constitution by the Constitutional Court, many decisions of the Constitutional Court were not carried out by other State Institutions or Government Agencies which have the obligation to follow up and implement the Constitutional Court Decisions. If the decision of the Constitutional Court is not implemented in the Unitary State of the Republic of Indonesia, it can legally interfere with the administration of government as a result of not implementing the decision of the Constitutional Court as a State Institution that has attribution authority in the 1945 Constitution of the Republic of Indonesia. Purposes of the Research: To analyze the Executive Power of the Decisions of the Constitutional Court which are final and binding in Indonesia Methods of the Research: The type of research used in this writing is normative juridical research. Results of the Research: The results show that the Constitutional Court's decision has executive power because it is final and binding when pronounced by the Constitutional Court Judge, and the Constitutional Court's decision actually has a juridical position as law and is used as a source of law by the DPR and the Government in forming laws. related to the decision of the Constitutional Court